Recovery of Education System in Myanmar - Tharaphi, Rita (FIA UB, 2019)
Myanmar’s education system is very weak with the least national budget allocation. The condition of physical infrastructure and human resource capacity of the system is also very poor without standard facilities and professional teachers. Whether in schools, colleges or universities, there is very few opportunities and little incentive for professional development. A process of recovery is getting underway, but it will take years before significant improvements for evidence. Major cultural change is required in the style of leadership and management at all levels of government, and there is also a desperate need for more financial resources. This paper documents the current state of the education system in Myanmar and advances certain priority areas for immediate attention.